2015
DOI: 10.11646/zootaxa.4040.2.1
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the rodent genus Hylomyscus from Angola, with a distributional summary of the H. anselli species group (Muridae: Murinae: Praomyini)

Abstract: A new species of Hylomyscus, H. heinrichorum, is described from mountains in western Angola. Based on morphological traits and cranial morphometry, the new species is assigned to the H. anselli species group and is hypothesized to be most closely related to H. anselli Bishop proper, a species named from Zambia. Members of both the H. anselli and H. denniae species groups occupy the Afromontane Biotic Zone, found in various mountain systems to the south and east of the Congo Basin. Evidence is reviewed that sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…anselli, originally described from northwestern Zambia, was considered by Carleton and Stanley (2005) to encompass Zambia and westernmost Tanzania. Our genetic data show that all specimens from western Tanzania mistakenly assigned to anselli by Carleton & Stanley (2005) and Carleton et al (2015) belong to a new genetically very distinct undescribed species here labeled as H. cf. anselli.…”
Section: -1 Systematics Taxonomy and Geographical Distributionmentioning
confidence: 72%
See 1 more Smart Citation
“…anselli, originally described from northwestern Zambia, was considered by Carleton and Stanley (2005) to encompass Zambia and westernmost Tanzania. Our genetic data show that all specimens from western Tanzania mistakenly assigned to anselli by Carleton & Stanley (2005) and Carleton et al (2015) belong to a new genetically very distinct undescribed species here labeled as H. cf. anselli.…”
Section: -1 Systematics Taxonomy and Geographical Distributionmentioning
confidence: 72%
“…Moreover, these two groups are not closely related. More recently, H. heinrichorum from the highlands of Angola was added to the anselli group (Carleton et al, 2015) resulting in four named species in this clade (anselli, arcimontensis, kerbispeterhansi and heinrichorum). anselli, originally described from northwestern Zambia, was considered by Carleton and Stanley (2005) to encompass Zambia and westernmost Tanzania.…”
Section: -1 Systematics Taxonomy and Geographical Distributionmentioning
confidence: 99%
“…Angolan is known for a fairly high number of endemic or near-endemic species, particularly in the case of rodents and shrews, where our study identified one shrew and six rodents endemic to the central and western Angolan highlands. The western escarpment Afromontane forests of Angola are particularly important as a centre of both species richness and endemism of plants and vertebrates including mammals (Carleton et al 2015). We suggest that future work should target more intensive surveys of small mammals in the central and western Angolan highlands to verify the presence and conservation status of threatened and/or endemic small mammal taxa.…”
Section: Discussionmentioning
confidence: 99%
“…The biodiversity of Serra da Neve remains largely undocumented with only two expeditions to it in the last few years ( Barker et al 2015 , this study), according to available literature. Other inselbergs and highlands found along the Angolan escarpment, including Mount Moco (Huambo Province) and the highlands of Gabela-Seles and the Kumbira Forest (Kwanza Sul Province), are known to harbor a significant number of endemics and relict populations of vari ous taxa ( Marx 1956 , Hall 1960 , Hall and Moreau 1970 , Huntley 1974 , Sekercioglu and Riley 2005 , Maiato 2009 , Mills 2010 , Mills et al 2011 , Cáceres et al 2015 , Carleton et al 2015 , Gonçalves and Goyder 2016 , Svensson et al 2017 ). While the biogeographic affinities of these areas are not completely understood, there is a general pattern of relictual distributions for taxa otherwise found in central or eastern Africa.…”
Section: Discussionmentioning
confidence: 99%